2004
DOI: 10.1007/bf03018429
|View full text |Cite
|
Sign up to set email alerts
|

Caudal neostigmine with bupivacaine produces a dose-independent analgesic effect in children

Abstract: P Pu ur rp po os se e: : To evaluate the analgesic efficacy and duration of varying doses of caudal neostigmine with plain bupivacaine and its side effects in children undergoing genito-urinary surgery. M Me et th ho od ds s: :In a randomized double-blind prospective study 80 boys aged two to eight years scheduled for surgical repair of hypospadias were allocated randomly to one of four groups (n = 20 each) and received either only caudal 0.25% plain bupivacaine 0.5 mL·kg -1 (Group I) or 0.25% plain bupivacain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 30 publications
(59 reference statements)
1
24
1
1
Order By: Relevance
“…It can treat myasthenia gravis and antagonize remnants of non‐depolarizing muscle relaxant in clinical anesthesia . Neostigmine increases the concentration of acetylcholine in the synapses and thus enhances acetylcholine‐mediated mechanisms of analgesia . It inhibits the activity of spinal cord dorsal horn Fos protein‐positive neurons relating to conduction of feelings of harm, inhibits central sensitization, blocks transmission of feelings of harm from the spinal cord, and produces antinociception .…”
Section: Discussionmentioning
confidence: 99%
“…It can treat myasthenia gravis and antagonize remnants of non‐depolarizing muscle relaxant in clinical anesthesia . Neostigmine increases the concentration of acetylcholine in the synapses and thus enhances acetylcholine‐mediated mechanisms of analgesia . It inhibits the activity of spinal cord dorsal horn Fos protein‐positive neurons relating to conduction of feelings of harm, inhibits central sensitization, blocks transmission of feelings of harm from the spinal cord, and produces antinociception .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the dose of caudal neostigmine was 2 μg/kg, as it was previously demonstrated to be effective dose in adults[8] and children. [910] Epidural neostigmine has been shown to potentiate opioids. In fact, in our present study, caudal sufentanil alone was no better than when administered in the IV route, and the caudal route would just be justified by the association of neostigmine, but not adrenaline in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Neostigmine has also been coadministered for caudal analgesia in children with bupivacaine [179][180][181] or ropivacaine, 182 where it was reported to provide prolonged analgesia without any adverse effects. This benefit was demonstrated in a double-blind, randomized, prospective study by Karaaslan and coworkers,183 whereby 60 male patients between the ages of 5 months and 5 years undergoing genitourinary surgery were allocated randomly to one of three groups.…”
Section: Cholinergic Agonists (Box 438)mentioning
confidence: 99%